Impact of Visual Pollution at the Entrances of Coastal Cities in Lebanon - Rola, Hijazi (European Scientific Journal, ESJ, 2019)
Visual pollution is a term given to unattractive visible elements such as non-thought-out buildings, unregulated architecture, street furniture, and random billboards. All these unattractive components have an effect on human eyes. The paper focuses on shedding light on the impact of visual pollution at the entrances of coastal cities in Lebanon to build a knowledge base for such pollution problem. Photographs were taken of the main entrances of Tyr, Saida, Beirut Byblos, and Tripoli through a camera installed on a car. These entrances were located using maps from Google, the municipality and other sources. The most important findings of this study were that cities’ entrances have been visually polluted in several ways especially with facades of buildings, advertising materials, lack of aesthetic elements, and lack of street furniture. The study recommended that municipalities should carry out several actions in order to improve the visual and aesthetic aspects of the coastal cities’ entrances. Creation of street furniture, organization of advertising boards, imposing of legislation and laws to regulate aesthetic aspects of building facades as well as promoting aesthetic education among the local community could help in mitigating the problems.